2015
DOI: 10.1088/0004-637x/809/1/36
|View full text |Cite
|
Sign up to set email alerts
|

The Southern Argentina Agile Meteor Radar Orbital System (Saamer-Os): An Initial Sporadic Meteoroid Orbital Survey in the Southern Sky

Abstract: We present an initial survey in the southern sky of the sporadic meteoroid orbital environment obtained with the Southern Argentina Agile MEteor Radar (SAAMER) Orbital System (OS), in which over three-quarters of a million orbits of dust particles were determined from 2012 January through 2015 April. SAAMER-OS is located at the southernmost tip of Argentina and is currently the only operational radar with orbit determination capability providing continuous observations of the southern hemisphere. Distributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 64 publications
(195 reference statements)
4
51
0
Order By: Relevance
“…Figure shows the radiant distribution of meteoroids impacting the Moon for four different Moon phases during the first lunation in our model (July–August 2013). The predicted radiant distributions are similar to what different radar and optical facilities observe at Earth (e.g., Campbell‐Brown, ; Janches et al, ; Jenniskens et al, ). The x axis in Figure is the LT at the Moon.…”
Section: Modeled Selenocentric and Temporal Variability Of Meteoroid supporting
confidence: 77%
See 2 more Smart Citations
“…Figure shows the radiant distribution of meteoroids impacting the Moon for four different Moon phases during the first lunation in our model (July–August 2013). The predicted radiant distributions are similar to what different radar and optical facilities observe at Earth (e.g., Campbell‐Brown, ; Janches et al, ; Jenniskens et al, ). The x axis in Figure is the LT at the Moon.…”
Section: Modeled Selenocentric and Temporal Variability Of Meteoroid supporting
confidence: 77%
“…It can be observed from this figure that for α = 3.4 our model can reproduce the LT distribution of M + observed by LDEX even for a scenario where there is no contribution from either JFC or OCC meteoroids, with HTC meteoroids being the sole source of lunar surface impacting meteoroids. However, decades of Earth‐based observations, ground‐based observations, and dynamical modeling have demonstrated that the fluxes of both JFC and OCC meteoroids should represent a significant portion of the incoming meteoroid flux at Earth (Campbell‐Brown, ; Fentzke & Janches, ; Janches et al, ; Nesvorný, Janches, et al, ; Nesvorný, Vokrouhlický, et al, ). Furthermore, Carrillo‐Sánchez et al () required a JFC‐to‐LPC ratio at Earth of 6.924.8+14 in order to simultaneously reproduce lidar observations of the vertical Na and Fe fluxes above 87.5 km and the measured cosmic spherule accretion rate at the South Pole.…”
Section: Constraining the Model With Ladee/ldex Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, for the case of meteor radars, this portion increases to where these populations do not represent more than ∼45% (see Table 2 in Janches et al 2015a). Thus, even though the results presented in Figure 8 show that the predicted detection rates at Arecibo are, in general, below the actual detected rates, for the case of smaller HE radius, they are nevertheless significantly higher than expected (∼71% of the observed counts).…”
Section: He Potential Aspect Sensitivitymentioning
confidence: 86%
“…To describe the contribution of long-period HTCs, we utilized the steady state model by Pokorný et al (2014), who used it to explain the origin of the toroidal meteoroid sources (Campbell-Brown & Wiegert, 2009;Janches et al, 2015;Jones & Brown, 1993). The toroidal meteoroids are characterized by high-ecliptic latitude radiants ( ∼ ±55 ∘ -60 ∘ ), both located north and south from the apex direction, impacting the Earth with a typical velocity of ∼35 km s −1 , and resulting in high-inclination preatmospheric orbits with respect to the ecliptic (∼70 ∘ ).…”
Section: Long-period Comet Models 221 Htc Modelmentioning
confidence: 99%